First record of the non-indigenous portunid crab charybdis variegata from the western atlantic coast - Sant’Anna, Bruno Sampaio; Watanabe, Timóteo Tadashi [UNESP]; Turra, Alexander; Zara, Fernando José [UNESP] (Regional Euro-Asian Biological Invasions Centre Oy (REABIC), 2012)
Biological invasions are a present and growing environmental problem because non-indigenous organisms may affect the structure and functioning of native communities. In the marine environment there are records of invasive species in almost all phyla, including crustaceans, and the portunid crabs of the genus Charybdis are among the most widespread invasive groups. We report the first record of Charybdis variegata (Fabricius, 1798) from the western Atlantic coast. This species was collected on an intertidal rocky shore near Santos Harbor, São Paulo state, Brazil. Of 311 portunid crabs sampled, 309 individuals belonged to the non-indigenous Charybdis hellerii (A. Milne Edwards, 1867), one was a native Cronius ruber (Lamarck, 1818), and one was identified as the non-indigenous Charybdis variegata. This individual was a juvenile female measuring 27.5 mm in carapace width. The taxonomic traits used for species identification, as well as a morphological comparison between C. hellerii and C. variegata are presented. The introduction route and establishment status of this species are also discussed.
Keywords: Alien species; Atlantic waters; Charybdis; Crustacea